QTL mapping for bioenergy traits in sweet sorghum recombinant inbred lines. Issue 11 (14th September 2021) - Souza, Vander Fillipe de; Pereira, Guilherme da Silva; Pastina, Maria Marta; Parrella, Rafael Augusto da Costa; Simeone, Maria Lúcia Ferreira; Barros, Beatriz de Almeida; Noda, Roberto Willians; da Costa e Silva, Luciano; Magalhães, Jurandir Vieira de; Schaffert, Robert Eugene; Garcia, Antonio Augusto Franco; Damasceno, Cynthia Maria Borges
Abstract: During the past decade, sweet sorghum ( Sorghum bicolor Moench L.) has shown great potential for bioenergy production, especially biofuels. In this study, 223 recombinant inbred lines (RILs) derived from a cross between two sweet sorghum lines (Brandes × Wray) were evaluated in three trials. Single-nucleotide polymorphisms (SNPs) derived from genotyping by sequencing of 272 RILs were used to build a high-density genetic map comprising 3, 767 SNPs spanning 1, 368.83 cM. Multitrait multiple interval mapping (MT-MIM) was carried out to map quantitative trait loci (QTL) for eight bioenergy traits. A total of 33 QTLs were identified for flowering time, plant height, total soluble solids and sucrose (five QTLs each), fibers (four QTLs), and fresh biomass yield, juice extraction yield, and reducing sugars (three QTLs each). QTL hotspots were found on chromosomes 1, 3, 6, 9, and 10, in addition to other QTLs detected on chromosomes 4 and 8. We observed that 14 out of the 33 mapped QTLs were found in all three trials. Upon further development and validation in other crosses, the results provided by the present study have a great potential to be used in marker-assisted selection in sorghum breeding programs for biofuel production.